Effect of Tilted Nanostructures on Anisotropic Wetting Behavior on PET Surfaces by Oxygen Plasma Modification - WANG Yitian, LI Yupeng, HUO Lei, LEI Mingkai (Cailiao Baohu)
In order to improve the wettability of polymer surfaces， oxygen plasma modification technology was used to treat the surface of polyethylene terephthalate (PET) under the condition of 200 W for 90 min using sample holders with inclination angles of 30°， 45° and 60°.The nanostructures with tilt angles and lengths of 32.5° and 2.36 μm，45.2° and 2.15 μm，59.5° and 2.00 μm were prepared， respectively.Anisotropic wetting of liquid droplets and directional flow behavior of liquid were studied on the PET surfaces after modified by plasma.Additionally，the direction opposite to the tilted nanostructure was referred to as the Y＋direction， the direction along the tilted nanostructure was referred to as the Y－ direction， and the direction perpendicular to Y± was referred to as the X± direction.Results showed that the contact angle of the droplet on the PET surfaces modified by plasma decreased， and the wetting length increased with the increase of inclination angle of the sample holders.Meanwhile， the static contact angle of the droplet in the X± direction was greater than that in the Y± direction，and the wetting length in the X± direction was smaller than that in the Y± direction.Continuous water injection was carried out on the PET surfaces modified by plasma.The droplets were pinned in the Y－ direction and flowed in the Y＋direction.Furthermore， the average flow velocities of droplets on the plasmamodified surface at 30°，45° and 60° inclination angles were 0.017 0，0.021 0 and 0.022 7 mm/s，respectively.Among them，the droplets on the PET surfaces after modified by plasma at 60° inclination angle had a flow velocity of 2.39 times that of the original surfaces in the Y＋direction.